Availability, diversity, uses and nutritional status of wild and semi wild plants from selected native markets of central Sarawak, Malaysia - Sahrir, Muhd Arif Shaffiq (2013)
Surveys on wild and semi-wild plants were conducted at four native markets (Bintulu, Sibu, Sarikei and Selangau) in central Sarawak. This study was to determine the availability, diversity, uses and the nutritional status of the wild and semi-wild plants. Edible parts of the plants were brought back to the laboratory and were subjected to proximate analyses, minerals and sugar contents based on the standard methods. A total of 49 wild and semi-wild plants were recorded with Sibu native markets have the highest number of plants species (40 species and 25 families). The most abundant plant family traded in the markets was Arecaceae (18.25 %) based on the trader involved. Forty five species of wild and semi-wild plants recorded were consumed as foods, two species (Helminthostachys zeylanica and Nephrolpeis biserrata) used for both food and medicine, two species (Myrmecodia tuberosa and Lycopodiella cernua) as medicine and two other species used as household items e.g., food wrapper (Licuala spinosa) and mosquito repellent (Goniothalamus velutinus). Based on the proximate analyses based on dry weight basis, the crude protein for fruits (0.04-3.17%), vegetables (0.14-2.98%) and seeds (1.06-4.69%). The crude fat content ranged from 0.04 to 18.06 % for fruits, 0.04 to 0.66% for vegetables and 1.23 to 34.18% for seeds. Leafy vegetables such as Ficus grossularioides provides good source of fiber (12.18%) while fruits provides good source of carbohydrate ranged from 70.54 to 96.99%. The minerals analyses indicated that ferns such Diplazium esculentum have high content of P, Na, Mg and Ca which provides good source of minerals with affordable price. The sugar contents (sucrose, fructose and glucose) of 11 fruits of wild and semi-wild plants were analysed using HPLC. Results indicated that most of the fruits analysed have high amount of glucose and fructose compared to sucrose. Artocarpus odaratissimus recorded significantly high amount of glucose (3.99 g per 100 g) and fructose (4.85 g per 100 g) compared to other wild fruits. Information on the nutritional status of wild and semi-wild plants also can help the agronomist in determining their potential as new crops and increase their function in local diets. Documentation of traditional knowledge on the uses of wild and semi-wild plants are important to provide information on consumption, various uses, mode of preparation and medicine for future utilization.